BENTUK DAN MAKNA UNGKAPAN BAHASA JEPANG DALAM NOVEL NORWEY NO MORI KARYA HARUKI MURAKAMI SEBAGAI ALAT INTERAKSI SOSIAL - Renny Anggraeny; Ni Made Wiriani (Universitas Pendidikan Ganesha, 2015)
In Japanese language, there are various greeting expressions according to the situation or season. Japanese people greet each other in many different ways depending on the relationship you have with the person you are greeting. Japanese can be roughly separated into three levels of politeness; casual, polite, and honorific/humble. Social status of speaker and listener should be considered. Japanese expressions are sometimes have difficulty to find a equivalent into Indonesian language. Therefore, to avoid language of mistakes , it is necessary to know how to use the Japanese expression correctly especially to Japanese learners. This research is the analysis of how to say greeting, thank you, apology expressions in Japanese and how the meaning of an expression of Japanese Language in the novel Norwey no Mori by Haruki Murakami. The method that used in this research is descriptive method. In analyzed form and the meaning of Japanese expressions, writer used Pateda theory (2001) and based on the concept of Edizal (2001), which analyzed how to equivalent the meaning of Japanese expression into Indonesian Language. The research result in novel Norwey no Mori by Haruki Murakami shows the usage of greeting or daily Japanese expressions are Chotto, Anata, Watashi, Iie (iya/uun), Wakaru dan wakaranai, Taihen, Anou, Sukoshi, Sayounara, Moshimoshi, Okagede, Kekkou. And the expressions for saying thank you and apology are Daijoubu, Arigatou, Gomennasai, Doumo. The data are then analyzed how to equivalent the meaning of Japanese expressions into Indonesian language based on formal, informal situation and Japanese cultural. Keywords: Japanese expression, greeting, thank you and apology expression